THE INFLUENCE OF COOPERATIVE LEARNING ‘THINK-TALK-WRITE’ AND LEARNING MOTIVATION TOWARD THE STUDENTS’ LEARNING RESULT OF DRAMA WRITING AT JUNIOR HIGH SCHOOL - Bunga Bunga; Harris Effendi Thahar; Novia Juita (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2014)
PENGARUH MODEL PEMBELAJARAN KOOPERATIF ‘THINK-TALK-WRITE’ DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MENULIS NASKAH DRAMA SISWA SLTP AbstractThis study aimed to clarify the effect of the model cooperatif learning strategies Think-Talk-Write and high motivation and low motivation to learn the study to write a drama students class VIII SMP Negeri 3 Batang Anai. The population was class VIII SMP Negeri 3 Batang Anai. Sampling totaled 63 students conducted by purposive sampling. Data collected through questionnaires and tests. Questionnaire used to see students' motivation and performance tests conducted to determine the result of study to write a drama of students. Analysis and discussion of the data is done in accordance with the descriptive-analytical study concept experiments. Based on the results of the data analysis we can conclude the following four things. First, the result of study to write a drama that taught using model cooperative learning strategies Think-Talk-Write better than students taught by conventional methods. Second, there is no interaction between learning motivation and learning methods in affecting student’ result of study to write drama. Third, the result of study to write a drama of students who have high motivation are taught using model cooperative learning strategies Think-Talk-Write better than that taught by convensional methods. Fourth, the result of study to write a drama of students who have low motivation are taught using model cooperative learning strategies Think-Talk-Write better than that taught by convensional method.Keywords: Cooperative Learning, Strategies Think-Talk-Write, Learning and Motivation, a Drama WritingAbstrakPenelitian ini bertujuan untuk memperjelas dampak model strategi pembelajaran kooperatif Think-Talk-Write dan motivasi belajar tinggi serta motivasi belajar rendah dalam menulis drama pada siswa kelas VIII SMP Negeri 3 Batang Anai. Populasi penelitian adalah kelas VIII SMP Negeri 3 Batang Anai. Sampel sebanyak 63 siswa dilakukan secara purposive sampling. Data dikumpulkan melalui kuesioner dan tes. Kuesioner yang digunakan untuk melihat motivasi dan tes kinerja siswa dilakukan untuk mengetahui hasil belajar menulis drama siswa. Analisis dan pembahasan data dilakukan sesuai dengan eksperimen konsep penelitian deskriptif-analitik. Berdasarkan hasil analisis data dapat disimpulkan empat hal berikut. Pertama, hasil belajar menulis drama yang diajarkan dengan menggunakan model strategi pembelajaran kooperatif Think-Talk-Write lebih baik daripada siswa yang diajarkan dengan metode konvensional. Kedua, tidak ada interaksi antara motivasi belajar dan metode pembelajaran dalam mempengaruhi hasil belajar siswa untuk menulis drama. Ketiga, hasil belajar menulis drama siswa yang memiliki motivasi tinggi diajarkan menggunakan model strategi pembelajaran kooperatif Think-Talk-Write lebih baik dari pada yang diajarkan dengan metode konvensional. Keempat, hasil penelitian untuk menulis drama siswa yang memiliki motivasi rendah diajarkan menggunakan model strategi pembelajaran kooperatif Think-Talk-Write lebih baik daripada yang diajarkan dengan metode konvensional.Kata kunci: Pembelajaran Kooperatif, Strategi Think-Talk-Write, belajar dan motivasi, Drama Menulis